(1549) بحث الصناعات الصغيرة التحضر والفقر والدخل الإقليمي فى مصر : دراسة لتحديد أولوية المحافظات والمناطق الحضرية بها لتوطين الصناعات الصغيرة. Research on small industries, urbanization, poverty, and regional income in Egypt: A study to determine the priority of governorates and their urban areas for the localization of small industries. - كيلانى، السيد محمد. (معهد التخطيط القومي, 2018)

(untitled)
يشتمل على إرجاعات ببليوجرافية.